$$\sin \alpha +\sin \beta =2\sin \frac{\alpha +\beta }{2}\cos \frac{\alpha -\beta }{2}, \sin \alpha -\sin \beta =2\cos \frac{\alpha +\beta }{2}\sin \frac{\alpha -\beta }{2}$$


$$\cos \alpha +\cos \beta =2\cos \frac{\alpha +\beta }{2}\cos \frac{\alpha -\beta }{2}, \cos \alpha -\cos \beta =-2\sin \frac{\alpha +\beta }{2}\sin \frac{\alpha -\beta }{2}$$


$$ tg \alpha \pm tg \beta =\frac{\sin (\alpha \pm \beta )}{\cos \alpha \cos \beta }, ctg \alpha \pm ctg \beta =\frac{\sin (\beta \pm \alpha )}{\sin \alpha \sin \beta }$$


$$ tg \alpha + ctg \beta =\frac{\cos (\alpha + \beta )}{\cos \alpha \sin \beta }, tg \alpha - ctg \beta =-\frac{\cos ( \alpha+\beta )}{\cos \alpha \sin \beta }$$


2010-12-11 • Просмотров [ 678 ]